Effort index as a novel variable for monitoring the level of effort during resistance exercises - Rodriguez-Rosell, D.; Yanez-Garcia, J. M.; Torres-Torrelo, J.; Mora-Custodio, R.; Marques, M. C.; González-Badillo, J. J. (The Journal of Strength and Conditioning Research, 2018)
This study aimed to analyze the acute mechanical and metabolic response to resistance exercise protocols (REPs) defined by 2 variables: the first repetition's mean velocity and the percentage of velocity loss (%VL) over the set. The product of these 2 variables was termed the effort index (EI) and was used as an indicator of the degree of fatigue induced during each REP. Twenty-one resistance-trained men (11 in full squat [SQ] and 10 in bench press [BP]) performed 16 REPs separated by 72 hours. Relative loads used (50, 60, 70, and 80% 1-repetition maximum) were determined from the load-velocity relationship for the SQ and BP, whereas volume was objectively determined using the %VL attained over the set (10, 20, 30, and 45% for SQ, and 15, 25, 40, and 55% for BP). Lactate concentration and velocity against the load that elicited a ~1.00 m/s (V1 m/s load) were measured before and after each REP. Post-exercise velocity with the V1 m/s load and lactate concentration were significantly different (P < 0.01-0.001) from pre-exercise after all REPs. A very close relationship was found between the proposed EI and %VL with the V1 m/s load (r = 0.92-0.98) and post-exercise lactate concentration (r = 0.91-0.95) in both exercises. The correlations between this new index and fatigue indicators such as VL allow us to gain further insight into the actual degree of effort incurred during resistance exercise. In addition to being a valuable addition for training monitoring, the proposed EI could also be used as an independent variable in training studies by equalizing the effort between different interventions.